Characterisation of Arabica coffee pulp - Hay from kintamani - Bali as prospective biogas feedstocks - Setyobudi, Roy Hendroko; Krido Wahono, Satriyo; Gamawati Adinurani, Praptiningsih; Wahyudi, Ahmad; Widodo, Wahyu Eko; Mel, Maizirwan; Adhi Nugroho, Yogo; Prabowo, Bayu; Liwang, Tony (EDP Sciences, 2018)
The huge amount of coffee pulp waste is an environmental problem. Anaerobic fermentation is one of the alternative solutions. However, availability of coffee pulp does not appear for year-round, whereas biogas needs continuous feedstocks for digester stability. This research uses coffee pulp from Arabica Coffee Factory at Mengani, Kintamani, Bali–Indonesia. The coffee pulp was transformed into coffee pulp-hay product by sun drying for preservations to extend the raw materials through the year. Characterization of coffee pulp-hay was conducted after to keep for 15 mo for review the prospect as biogas feedstocks. Several parameters were analyzed such as C/N ratio, volatile solids, carbohydrate, protein, fat, lignocellulose content, macro-micro nutrients, and density. The review results indicated that coffee pulp-hay is prospective raw material for biogas feedstock. This well-proven preservation technology was able to fulfill the continuous supply. Furthermore, some problems were found in the recent preliminary experiment related to the density and fungi growth in the conventional laboratory digester. Further investigation was needed to implement the coffee pulp – hay as biogas feedstocks.